MCIR1: A patient‐derived mantle cell lymphoma line for discovering new treatments for ibrutinib resistance. (18th July 2021) - Wu, Xiaosheng; Nowakowski, Kevin E.; Abeykoon, Jithma P.; Manske, Michelle; Stenson, Mary J.; Timm, Michael M.; Hanson, Curtis A.; Van Dyke, Daniel L.; Dasari, Surendra; Witzig, Thomas E.
Abstract: Background: Despite the unprecedented success of ibrutinib in lymphoma therapy, the development of ibrutinib resistance due to acquired BTK or PLCγ2 mutations has become a new clinical problem. However, not all resistance is mediated by these mutations and these mechanisms are poorly understood due to a lack of study tools that truly recapitulate this clinical scenario. Methods: We established a novel patient‐derived ibrutinib‐resistant mantle cell lymphoma (MCL) line named MCIR1. Using immunological, molecular, and cytogenetic approaches, we comprehensively characterized MCIR1 and further demonstrated its utility in the study of resistance mechanisms and treatments to overcome this resistance. Results: We show that MCIR1 is a bona fide ibrutinib‐resistant MCL cell line with normal BTK‐/PLCγ2 but ibrutinib‐resistant ERK1/2 and AKT1 signaling. RNA‐Seq analysis revealed a robust non‐canonical NF‐kB signaling that drives the ibrutinib resistance. We also demonstrate the potential utility of a MCIR1‐based cell and mouse model for the discovery of new treatments to overcome BTK inhibitor resistance. Conclusions: We have established the first patient‐derived ibrutinib‐resistant MCL cell line MCIR1 that lacks BTK or PLCγ2 mutations but exhibits a hyperactive non‐canonical NF‐kB pathway. We further demonstrate its utility in the discovery and validation of new drugs to overcome this resistance.